2014
DOI: 10.1007/s13277-014-2138-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-520a-5p displays a therapeutic effect upon chronic myelogenous leukemia cells by targeting STAT3 and enhances the anticarcinogenic role of capsaicin

Abstract: Aberrant expression profiles of microRNAs (miRNAs) have been previously demonstrated for having essential roles in a wide range of cancer types including leukemia. Antiproliferative or proapoptotic effects of capsaicin have been reported in several cancers. We aimed to study miRNAs involved in the Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway in chronic myeloid leukemia cell model and the effects of the capsaicin treatment on cell proliferation and miRNA regulation. miR-520… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…signaling. Previous research has confirmed that capsaicin regulates the expression of various miRNAs, such as miR-34a (16) and miR-520-5p (17). Firstly, we detected miR-449a expression in several AR-positive PCa cell lines.…”
Section: Restoration Of Mir-449a Expression Induced By Capsaicin Medimentioning
confidence: 62%
See 1 more Smart Citation
“…signaling. Previous research has confirmed that capsaicin regulates the expression of various miRNAs, such as miR-34a (16) and miR-520-5p (17). Firstly, we detected miR-449a expression in several AR-positive PCa cell lines.…”
Section: Restoration Of Mir-449a Expression Induced By Capsaicin Medimentioning
confidence: 62%
“…Chakraborty et al found that increased miR-34a expression by capsaicin decreased the survival advantage and enhanced Bax-dependent apoptosis in non-small cell lung cancers (16). Kaymaz et al proved that capsaicin suppressed the growth of chronic myelogenous leukemia cells by decreasing expression of miR-520a-5p which was shown as a probable oncogene (17). They also found that inhibition of miR520-5p enhanced the antitumor effect of capsaicin.…”
Section: Discussionmentioning
confidence: 99%
“…JAK/STAT3 pathway is shown to be a key mechanism to mediate cryptotanshinone-induced apoptosis of CML K562 cells (27). Besides, capsaicin can induce apoptosis and inhibit proliferation of K562 leukemic cells through affecting miR-520a-5p/STAT3 interaction (28). Bortezomib can induce apoptosis of K562 leukemic cells by interacting with JAK/STAT pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin has attracted considerable attention because of its chemoprotective properties against certain carcinogens and mutagens [13] . In addition, capsaicin has been reported to induce cell apoptosis in several tumor types, such as myeloid leukemia, colon cancer, and HCC [14][15][16][17] . The www.chinaphar.com Zhang SS et al Acta Pharmacologica Sinica mechanisms whereby capsaicin induces cancer cell apoptosis were reported to be either dependent or independent on the transient receptor potential vanilloid 1 (TRPV1) channel that serves as a direct target of capsaicin [18,19] .…”
Section: Introductionmentioning
confidence: 99%